Algunas características adaptativas de la flora vascular de los bosques de Tierra de Fuego, Argentina - Sebastià M.T.; Gutiérrez E. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
Some characteristics of the vascular flora of the forest region in the Argentinean part of Tierra de Fuego are analysed. The discussion is done in terms of its adaptive significance in relation to climatic and general edaphic conditions, the type of peculiarities under the forest canopy, and the characteristics of the fauna. The biological spectrum is in relation to the climatic conditions of the area, mainly in front of freezing, and to the microclimate of the forest. The floral biology and the pollination spectra are in relation to the low density and diversity of the unspecialised insects. The advantages of colonisation and the low density of species in the understory may are the cause of the so high proportion of autogamous and the low number of dioccious species. Zoochory is the predominant type of fruit dispersion, and can be in relation to the forest type ecosystem and to the high diversity.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)